Supine blood pressure normalised by daytime series values is independently associated with ischaemic wake-up stroke - Kamil Kowalczyk; Mariusz Kwarciany; Krzysztof Narkiewicz; Bartosz Karaszewski; Dariusz Gąsecki (Blood Pressure, 2022)
Purpose Wake-up stroke constitutes up to 1/4 of all ischaemic strokes; however, its pathomechanisms remain largely unknown. Although low nocturnal blood flow may be the underlying cause, little is known about blood pressure (BP) characteristic of wake-up stroke patients. The aim of our study was to look for differences in BP variables between wake-up stroke and known-onset stroke patients and to seek BP indices which could distinguish wake-up stroke patients from other stroke patients. Materials and Methods In the study, we included ischaemic stroke patients in whom office BP measurement and Ambulatory BP monitoring (ABPM) were recorded at day 7, after acute hypertensive response. The daytime period was defined as the interval from 6 a.m. to 10 p.m. From ABPM, we obtained parameters of BP variability. Additionally, we calculated the BP percentage differences defined as (supine office BP–average daytime BP)/average daytime BP for systolic, diastolic, and mean blood pressure. We calculated analogous indices for night-time. The univariate and multivariate relationships between BP variables and wake-up stroke were analysed. Results Among the recruited 120 patients (aged 61.6 ± 12.3; 88 [73%] males; the baseline National Institutes of Health stroke scale score 4 [3–8]), 36 (30%) had wake-up stroke. In a univariate analysis, the systolic and mean daytime and night-time BP differences were significantly lower in patients with wake-up stroke [(−1.92 (−11.55 to 3.95) vs 4.12 (−2.48 to 11.31), p = 0.006 and −6.20 (−12.32 to 7.42) vs 2.00 (−6.86 to 11.65), p = 0.029 for daytime, respectively; 0.00 (−9.79 to 11.82) vs 9.84 (0.00 to 18.25), p = 0.003 and 0.51 (−8.49 to 12.08) vs 7.82 (−2.47 to 20.39), p = 0.026, for night-time, respectively]. After adjustment for possible confounders, the systolic BP difference remained significantly associated with wake-up stroke (odds ratio = 0.96, 95% confidence interval = 0.92–1.00, p = 0.039). Conclusion The subacute office-ambulatory BP difference including the dynamic (systolic BP), but not static BP component was independently associated with wake-up stroke.